STUDI KOMPARASI PRAKTEK TRANSPARANSI DALAM PENGELOLAAN PERUSAHAAN DAERAH PASAR SURYA SURABAYA - Yuliastuti Rahayu (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2008)
Requirement of transparency in all sector is unavoidable, not only in governance but also at public company or regional company especially in carrying out the principles and appropriate policy in accordance with Good Corporate Governance standard.The good corporate governance principles determined by The Minister of ‘BUMN’ consist of: The transparency, Independence, Accountability, Responsibility and Fairness. In the case of transparency, ‘Bapepam’ give an example of the transparency practice for the public company. Some regulation of the transparency practice consist of: (1) Open information, (2) The quality of information, (3) The involvement of competence, (4) The supporter profession, (5) The limit of transaction material and the transaction of conflict interest, (6) Independent Commissary, and (7) Law Enforcement. The regional company of ‘Pasar Surya’ is the public company owned by the local Government in Surabaya. The writer is interested in uncovering whether ‘Pasar Surya’ has done the transparency what society desires. As the comparison, the writer uses the base regulations of the transparency practice for the public company. The writer pays attention to the characteristic difference at each company. The transparency practice which ‘Pasar Surya’ has done is in accordance with The Regional Regulation and The Mayor’s Decision.Basically ‘Pasar Surya’ has done the transparency activity but it is necessary to re-examine to get the target of good corporate governance.